First lord's fury [compact disc, unabridged] - Butcher, Jim, 1971- (Butcher, Jim, 1971- Codex Alera, 2009)
In the sixth installment of Jim Butcher's Codex Alera series, the savage Vord are on the march, and Gaius Octavian, the rightful First Lord of Alera, must lead his legions to the Calderon Valley to stand against them-using all of his intelligence, ingenuity, and furycraft to save their world from eternal darkness.